STRATEGI SEKOLAH DALAM MENINGKATKAN KUALITAS LULUSAN (STUDI KASUS SMPMPURI ARTHA MENGENAI STRATEGI KELULUSAN DAN CAPAIAN) - Zerlindah, Shakilla; Mustofa, Abdul; Thooriq, Annisa; Ayu Kartika, Titik; Permana, Hinggil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of graduate competency standards at SMP Puri Artha, which include the aspects of attitude, knowledge, and skills. The problem addressed in this research is how the school ensures that students achieve these competencies through structured, measurable, and continuous learning programs. This study employed a qualitative approach with a case study design. Data were collected through interviews with teachers, observation of learning activities, and analysis of school documents. The findings show that the school applies an integrated strategy to develop student competencies holistically. Attitude development is carried out through routine worship practices, religious education, social programs, and a discipline point system known as Gerakan Disiplin Sekolah (GDS). Knowledge competence is strengthened through a morning literacy program, digital-based learning, and the use of interactive media. Skill development is facilitated through the Digi Life Skill program, extracurricular activities, and hands-on practice. Competency evaluation is conducted regularly during mid-semester and final-semester assessments. This study also highlights the central role of teachers supported by principals, counselors, parents, and the school environment in achieving the intended learning outcomes. In conclusion, the strategy implemented by SMP Puri Artha emphasizes a balanced approach between academic achievement and the development of attitude, knowledge, skill, and physical health, in order to prepare graduates with comprehensive readiness for future challenges.